Shug Avery: A Reverberating Voice against Patriarchy in The Color Purple - Chapagaee, Rajendra Prasad (Innovative Research Journal, 2025)
The socio-cultural situation of the Negroes/African-American people, gender inequality, gender discrimination along with abuse and the themes of love and sexuality are brought about by Alice Walker in her novel The Color Purple. Shug Avery as a character and Shug Avery’s life and world views defy all these assumptions made upon African- American patriarchal society. Her rebellious nature and her relationship with Celie demand close reading to discover her multiple dimensions of her personality. In this paper,an attempt has been made to divulge Shug Avery’s personality, early life experiences and her actions that proves her an empowered color woman of racial oppressive patriarchal society. She has been studied especially for her rejection of male domination and empowered women to fight against male supremacy of African-American society. Shug Avery as a character and her relationship with Celie takes us closer to seeing the portrayal of color women. This paper lays especial focus on how Shug evolves herself as empowered color woman and how she makes her voice as a reverberating voice Against Patriarchy through her actions.it also studies how Shug supports color , especially the protagonist, Celie to empower herself. The paper also deals with the themes of love and sexuality, religion along with Shug Avery’s personality, early life experiences and the roles she played to empower color women.